INTEGRATING ISLAMIC PEDAGOGY WITH 21ST CENTURY SKILLS: A CONCEPTUAL FRAMEWORK FOR GLOBAL ISLAMIC EDUCATION - Septian Arief Budiman; Fil Isnaeni (As-Sulthan Journal of Education, 2025)
This research examines the integration of Islamic pedagogy and 21st-century skills as an effort to establish a globally relevant conceptual framework for Islamic education. The scope of the study includes an analysis of the core principles of Islamic pedagogy, such as adab, hikmah, and tazkiyah, and how these principles can be adapted to address the challenges of modern education, including digital literacy, critical thinking, and cross-cultural collaboration. The aim of this research is to formulate an integrative model that can serve as a reference for the development of curricula and teaching methods in contemporary Islamic educational institutions. The methodology employed is qualitative research with a systematic literature review approach, accompanied by a comparative analysis of classical and contemporary Islamic education literature. The findings indicate that there are significant points of convergence between the values of Islamic education and 21st-century skills, particularly in the areas of character building, work ethics, and social competencies. The conclusion of this research asserts that such integration is not only feasible but also crucial to meet the needs of Islamic education in the era of globalization and digital disruption.